2021
DOI: 10.3390/cancers13092048
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants for Prediction of Outcome of Patients with Papillary Thyroid Carcinoma

Abstract: Papillary thyroid carcinoma (PTC) usually presents an excellent prognosis, but some patients present with aggressive metastatic disease. BRAF, RAS, and TERT promoter (TERTp) genes are altered in PTC, and their impact on patient outcomes remains controversial. We aimed to determine the role of genetic alterations in PTC patient outcomes (recurrent/persistent disease, structural disease, and disease-specific mortality (DSM)). The series included 241 PTC patients submitted to surgery, between 2002–2015, in a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 66 publications
3
23
0
1
Order By: Relevance
“…Studies by Povoa et al. ( 60 ) and Melo et al. ( 61 ) analyzed the association of TERT and BRAF mutations with distant metastasis in PTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Povoa et al. ( 60 ) and Melo et al. ( 61 ) analyzed the association of TERT and BRAF mutations with distant metastasis in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in PTC by Melo et al(58) and others(37,55,59), where they show that TERT promoter mutations are a marker for DM. Studies by Povoa et al(60) andMelo et al (…”
mentioning
confidence: 95%
“…On the contrary, Povoa et al and Xing et al found no relation between mutation and poorer prognosis. Most patients with RAS mutation alone had a stage I diagnosis, usually presenting excellent responses to therapy, and were free of disease at the end of follow-up [ 42 , 43 ].…”
Section: Genetic Aberrations Markersmentioning
confidence: 99%
“…On genetic analysis, the occurrence of BRAF and RAS mutations are uncommon events in DSVPTC and activation of RET/PTC rearrangements are common (9). Genetic detection is not only crucial to the diagnosis for PTC, and also used to assess the prognosis (10,11). When the morphology is atypical, genetic detection can be of great help to pathologists.…”
Section: Introductionmentioning
confidence: 99%